The influence of brand image, food delivery service, content creator credibility and price on cimory product purchasing decisions - Sabrina Khoirun Nisha Brina; Khamdan Suriyok (Institute of Computer Science (IOCS), 2023)
Cimory is a brand of fermented milk products which is quite popular in Indonesia. In selling its products, Cimory uses various marketing strategies, such as expanding its reach through delivery services. On the other hand, the phenomenon of social media also has a significant influence on consumer attitudes. Content creators who have great credibility can influence consumer purchasing decisions. This research is expected to provide a more in-depth explanation of the factors that influence consumer purchasing decisions on Cimory products, so that it can help the company in designing a more effective marketing strategy. This type of research is quantitative research. The method used in this study was purposive sampling. Based on the results of the study, it shows that the independent variables Brand Image, Food Delivery Service, Content Creator Credibility and Price simultaneously influence purchasing decisions. Partially the independent variables Brand Image, Food Delivery Service and Content Creator Credibility and Price influence Purchasing Decisions. Then companies can improve consumer purchasing decisions by building better relationships with customers, and increase their overall business profits.ease with which interested parties can locate our article.